Plant immunity in plant–aphid interactions - Jaouannet, Maëlle; Rodriguez, Patricia A.; Thorpe, Peter; Lenoir, Camille J. G.; MacLeod, Ruari; Escudero-Martinez, Carmen; Bos, Jorunn I.B. (Frontiers in Plant Science, 2014)
Aphids are economically important pests that cause extensive feeding damage and transmit viruses. While some species have a broad host range and cause damage to a variety of crops, others are restricted to only closely related plant species. While probing and feeding aphids secrete saliva, containing effectors, into their hosts to manipulate host cell processes and promote infestation. Aphid effector discovery studies pointed out parallels between infection and infestation strategies of plant pathogens and aphids. Interestingly, resistance to some aphid species is known to involve plant resistance proteins with a typical NB-LRR domain structure. Whether these resistance proteins indeed recognize aphid effectors to trigger ETI remains to be elucidated. In addition, it was recently shown that unknown aphid derived elicitors can initiate ROS (reactive oxygen species) production and callose deposition and that these responses were dependent on BAK1 (BRASSINOSTERIOD INSENSITIVE 1-ASSOCIATED RECEPTOR KINASE 1) which is a key component of the plant immune system. In addition, BAK-1 contributes to nonhost resistance to aphids pointing to another parallel between plant-pathogen and –aphid interactions. Understanding the role of plant immunity and non-host resistance to aphids is essential to generate durable and sustainable aphid control strategies. Although insect behavior plays a role in host selection and non-host resistance, an important observation is that aphids interact with nonhost plants by probing the leaf surface, but are unable to feed or establish colonization. Therefore, we hypothesize that aphids interact with nonhost plants at the molecular level, but are potentially not successful in suppressing plant defenses and/or releasing nutrients.